On outer measures and semi-separation of lattices - Robert W. Schutz (International Journal of Mathematics and Mathematical Sciences)
This present paper is concerned with set functions related to {0,1} two valued measures. These set functions are either outer measures or have many of the same characteristics. We investigate their properties and look at relations among them. We note in particular their association with the semi-separation of lattices.